บทละครโต้กลับ : การวิพากษ์วรรณกรรมเอกของยุโรป - ดนยา ทรัพย์ยิ่ง (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
To analyze the techniques and themes in three counter-discursive plays: Aime Cesaire s Une Tempete, Derek Walcott s Pantomime and David Henry Hwang s M. Butterfly. These techniques and themes function as strategies to expose ethnic prejudices and power relations in three selected European canonical works: William Shakespeare s The Tempest, Daniel Defoe s Robinson Crusoe and Giacomo Puccini s madama Butterfly. The study shows that the three European works represent racial biases by constructing non-European characters as the inferior "other" to European characters. These biases are part of the binary opposition that is based upon the difference between "white-black", "master-slave" and "man-woman". The opposition entails a violent hierarchy that underlines non-European inferiority as against European superiority. Such biases are disquised by the canon formation as a symbol of literary greatness and valorization of European culture. Cesaire, Walcott and Hwang create counter-discursive plays in order to decolonize the mind from the European cultural hegemony. They deconstruct representations of authority in the European canon by rewriting plots, contexts, characters, and genres of the canonical texts, and by combining these elements with features of literary traditions of their indigenous cultures as part of their efforts to reconstruct their cultural identities. Different strategies are employed to subvert the racial biases: Cesaire opposes European and non-European characters so as to reverse the hierarchy to show the positive blackness light; and Walcott and Hwang present all fixed images as illusions.